Hungary: Orban’s atypical programme of solving the crisis - Đurković Miša (Međunarodni Problemi, 2011)
The article deals with the political and economic situation in Hungary in the last several years. The author firstly points to the causes of decline of influence of the previous socialist government and the heavy defeat of the socialists in the 2010 elections and the success of the right party Fidesz. After winning the elections, the Viktor Orban government started, at an accelerated rate, to implement the pre-election programme of Fidesz that had been prepared for a long time while it was an opposition party. The author is of the opinion that this programme is atypical, very radical and unique by many characteristics in the Europe of today. He points out that only a year after Fidesz victory the government and the parliament adopted quite a number of laws, a new Constitution and a set of risky measures of recovery that should lead to a substantial economic reform. The author particularly underlines the fact that the government decided to break of negotiation with IMF, reject its recommendations and try to overcome over-indebtedness by carrying out its own ideas.